2010
DOI: 10.1245/s10434-010-1199-5
|View full text |Cite
|
Sign up to set email alerts
|

Para-aortic Lymphadenectomy in the Management of Preoperative Grade 1 Endometrial Cancer Confined to the Uterine Corpus

Abstract: Background. The aim of this study was to determine the risk of para-aortic lymph node metastasis in surgically staged patients presenting with preoperative grade 1 endometrial cancer and to assess the impact of para-aortic lymphadenectomy. Materials and methods. A total of 131 consecutive patients diagnosed with preoperative grade 1 endometrial cancer from 2004 to 2009 were analyzed. We included women with endometrial cancer that was thought preoperatively to be confined to the uterine corpus, and all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…13,14 Patients at low-risk could have isolated PALN involvement, without concurrent pelvic node metastasis. 15 Todo et al 16 demonstrated that PALN dissection had a survival benefit for the intermediate and high-risk cases. However, PALN dissection failed to show any survival advantage in the low-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Patients at low-risk could have isolated PALN involvement, without concurrent pelvic node metastasis. 15 Todo et al 16 demonstrated that PALN dissection had a survival benefit for the intermediate and high-risk cases. However, PALN dissection failed to show any survival advantage in the low-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, the threshold for considering a staging complete is a lymph node count ≥20 with systematic para-aortic lymphadenectomy up to the renal vessels. As indicated in our previous study and in other studies, pelvic and para-aortic lymphadenectomy should be performed in all patients with endometrial cancer, because the preoperative grade 1 endometrial cancer is found to have upgraded disease and with para-aortic nodal metastasis, especially in the setting of preoperative CA-125 levels of ≥31 U/ml and deep myometrial invasion by magnetic resonance imaging [35]. Also there is no reliable preoperative and intraoperative evaluation to predict low-risk disease [36].…”
Section: Discussionmentioning
confidence: 93%
“…Yoon et al [ 45 ] staged 131 low-risk patients with endometrial cancer. All patients were preoperatively presumed to be grade 1, stage 1 and histologically confirmed as endometrioid carcinoma.…”
Section: Resultsmentioning
confidence: 99%